Pertanggungjawaban Pelanggaran Hak Cipta Dalam Penjualan Buku Bajakan Oleh Platform E-Commerce (Tokopedia) Berdasarkan Hukum Positif Indonesia - Muh. Ainul Maulana M; Muhammad Sood (Departement Business Law, Faculty of Law, University of Mataram, 2024)
The objective of this study is to explore the legal protection and liability for copyright infringement regarding the sale of pirated books on the e-commerce platform Tokopedia under Indonesian positive law. This study adopts normative legal research methods employing statutory and conceptual approaches. The findings indicated that legal protection for book creators covers both preventive and punitive measures. Furthermore, Tokopedia's liability for trading pirated books on its e-commerce platform is collective liability, which implies that the e-commerce entity, as a legal entity, is responsible for violations committed by business entities selling on its platform. The liability of e-commerce businesses is stipulated in several laws, such as the copyright law, the electronic information and transaction law, and government regulations on trade through electronic systems.